CHANGES IN THE CARDIOVASCULAR SYSTEM AND LIPID SPECTRUM OF BLOOD IN ADOLESCENTS WITH ARTERIAL HYPERTENSION (dynamics in a 20-year catamnesis) - Nikonova, Viktoriia (Sworld-Us Conference proceedings, 2025)
The work considers the peculiarities of changes in the morpho-functional parameters of the heart and the lipid spectrum of blood, which are formed in adults in which hypertension was formed in adolescence. Studies indicate the progressive development of m